Formulación del proceso de Gestión Secretaría General y subproceso de Gestión Documental en Secretaría General de la Universidad Nacional de Loja - Apolo Rios, Jordy Michael (2022)
The purpose of this project is to formulate the process and sub-process in support of Documentary Management in the General Secretariat Unit, establishing a necessary support guide for the development of processes, because based on the new Organic Regulation of Organizational Management by Processes of the National University of Loja to identify the procedure of the same, it generates confusion and a difficult understanding of the processes, therefore the idea of establishing a guide arises, in order to generate structure and ease in the procedures performed by the unit. The preparation of the Documentary Management Manual for the General Secretariat will allow for an effective management of the processes, minimize errors and improve the fluidity of the procedures, in order to streamline the activities carried out by the officers and facilitate the understanding and application of the processes in an effective and efficient manner. In the methodology, it was approached from the qualitative approach through the action research starting from the exploration of the information and application of interviews to those involved in the process and the observation sheet to carry out the information gathering of the process and sub-processes performed in the General Secretariat with respect to the Documentary Management and if the existing regulations are applied regarding the processes that are established within the same and how they must be complied with; The process survey methodology provided by the Universidad Nacional de Loja was applied prior to the preparation of the process manual and it was socialized with those involved in the process. As for the results obtained, a proposal for a manual of the General Secretariat Management process and Document Management subprocess was prepared and socialized with the officials responsible for the General Secretariat Unit of the Universidad Nacional de Loja for its validation.